Secular equilibrium assessment in a CaWO4 target crystal from the dark matter experiment CRESST using Bayesian likelihood normalisation. (April 2023) - Angloher, G.; Banik, S.; Benato, G.; Bento, A.; Bertolini, A.; Breier, R.; Bucci, C.; Burkhart, J.; Canonica, L.; D'Addabbo, A.; Di Lorenzo, S.; Einfalt, L.; et al.
Abstract: CRESST is a leading direct detection sub-GeV c − 2 dark matter experiment. During its second phase, cryogenic bolometers were used to detect nuclear recoils off the CaWO4 target crystal nuclei. The previously established electromagnetic background model relies on Secular Equilibrium (SE) assumptions. In this work, a validation of SE is attempted by comparing two likelihood-based normalisation results using a recently developed spectral template normalisation method based on Bayesian likelihood. Albeit we find deviations from SE in some cases we conclude that these deviations are artefacts of the fit and that the assumptions of SE is physically meaningful. Highlights: Novel assessment of secular equilibrium assumptions in a CaWO4 cryogenic crystal. Bayesian likelihood normalisation method of spectral templates. Comparison between fits with and without secular equilibrium assumptions. Deviations found -> effects of the fit; SE assumptions validated.